Verskillende benaderings tot opleiding in bestuurskole en besondere behoeftes in Suid-Afrika - Andre Morkel (South African Journal of Business Management, 1976)
Business schools in South Africa are exposed to many often conflicting demands which create particular challenges for excellence and adaptation. The local schools are constantly compared with the very best in the world as executives frequently attend top business schools overseas or attend seminars by visiting overseas business teachers. Participants on business school programs demand up to date high quality teaching. As departments of universities they are in addition subjected to the normal university traditions. Overseas models of business schools include the functional approach adopted by most large universities overseas, the diagnostic case study approach and underlying discipline approach. A variety of other models combining elements of the basic approach also exist. It is important for South African business schools to investigate various approaches to business school education and devise own approaches appropriate to their particular needs. Regular exchange of faculty members with overseas business schools is essential for many reasons as is actively pursued by most local business schools. The remaining need which is the essential final step to maturity is active research in business, management and organization with development concepts, theory and application. This is a rapidly growing activity at South African business schools and must be strongly encouraged.